The Role of Management Accounting in Sustainability - MEDIATY; USMAN, ASRI; RUSTAM, YUNDA DWI PUTRI; RAHMADANI M, AULIA; HASAN, ANNISA NABILA (International Journal of Multidisciplinary Research and Studies, 2023)
The background of this research is that economic development in the era of globalization requires every company to strategize to increase the ability to compete globally. Responding to environmental and social issues that occur in business encourages the role of management accounting to encourage corporate sustainability. The purpose of the problem in this study is to find out how management accounting helps companies achieve sustainability. This study also discusses what management accounting approaches are used. The research method used is the systematic literature review (SLR) method with a total of 27 Scopus articles using the Watase tool. The results showed that environmental management accounting (EMA) is one of the most widely used management accounting approaches according to previous research. In addition, the use of corporate management accounting can provide appropriate strategies related to the quality of service and production processes of the company to encourage the sustainability of the company.